Advances in Clinical and Biomedical Applications of Photoacoustic Imaging - Su, Jimmy L. (2010)
IMPORTANCE OF THE FIELD: Photoacoustic imaging is an imaging modality that derives image contrast from the optical absorption coefficient of the tissue being imaged. The imaging technique is able to differentiate between healthy and diseased tissue with either deeper penetration or higher resolution than other functional imaging modalities currently available. From a clinical standpoint, photoacoustic imaging has demonstrated safety and effectiveness in diagnosing diseased tissue regions using either endogenous tissue contrast or exogenous contrast agents. Furthermore, the potential of photoacoustic imaging has been demonstrated in various therapeutic interventions ranging from drug delivery and release to image-guided therapy and monitoring. AREAS COVERED IN THIS REVIEW: This article reviews the current state of photoacoustic imaging in biomedicine from a technological perspective, highlights various biomedical and clinical applications of photoacoustic imaging, and gives insights on future directions. WHAT THE READER WILL GAIN: Readers will learn about the various applications of photoacoustic imaging, as well as the various contrast agents that can be used to assist photoacoustic imaging. This review will highlight both pre-clinical and clinical uses for photoacoustic imaging, as well as discuss some of the challenges that must be addressed to move photoacoustic imaging into the clinical realm. TAKE HOME MESSAGE: Photoacoustic imaging offers unique advantages over existing imaging modalities. The imaging field is broad with many exciting applications for detecting and diagnosing diseased tissue or processes. Photoacoustics is also used in therapeutic applications to identify and characterize the pathology and then to monitor the treatment. Although the technology is still in its infancy, much work has been done in the pre-clinical arena, and photoacoustic imaging is fast approaching the clinical setting.